Bacteria in Sediments in a Seagrass Bed in Kauswagan, Lanao del Norte (Mindanao, Philippines) - Rosales-Apao, Patricia (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
Benthic bacteria found in the muddy sediments of a seagrass bed in the coastal wa!ers of Ka_uswa an, Lanao del Norte were studied. Sediment samples were taken during low tide with the use of a modified core out of a plastic syringe. Three senes of sample dtlution were made and aliqupts were prepared isolated and cultured. Results of the morphological, cultural and physiological tests showed six bactena belonging to five (5) genera, namely: Vibrio parahaemolyticus, V. cholerae, Pseudomonas, Bacillus, Salmonella and Shigella. No conclusive evidence could be said on the origin of the bacteria nor of the number of species found due to limited method available for identification. The bactenal flora may show the type of sediment and heterotrophic activities occurring in the seagrass sediments.